2002
DOI: 10.1093/ndt/17.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Severe evolution of chronic hepatitis C in renal transplantation: a case control study

Abstract: Using conventional immunosuppressive regimen, renal transplantation is associated with a more severe evolution of chronic hepatitis C as compared with HCV-infected immunocompetent subjects. Thus, the histopathological evaluation should be performed and anti-viral therapy discussed before renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 31 publications
2
66
1
1
Order By: Relevance
“…Data in the dialysis population are scant, and there are conflicting results from studies examining sequential posttransplant biopsies without the benefit of pretransplant samples. Using a matched immunocompetant control group, Zylberberg et al 39 reported more rapid progression of liver fibrosis in renal transplant recipients, whereas Alric et al 40 found just the opposite, with slower progression in the transplanted cohort. Interestingly, Kamar et al 41 reported variable outcomes including progression, stability, and even improvement in liver fibrosis among patients who underwent more than one post-transplant liver biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…Data in the dialysis population are scant, and there are conflicting results from studies examining sequential posttransplant biopsies without the benefit of pretransplant samples. Using a matched immunocompetant control group, Zylberberg et al 39 reported more rapid progression of liver fibrosis in renal transplant recipients, whereas Alric et al 40 found just the opposite, with slower progression in the transplanted cohort. Interestingly, Kamar et al 41 reported variable outcomes including progression, stability, and even improvement in liver fibrosis among patients who underwent more than one post-transplant liver biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, protocol liver biopsies within 6-12 months of transplantation, with subsequent biopsies based on clinical course, are required for evaluation of liver disease after transplantation (53). The prevalence of cirrhosis has been reported to be 5%-21% after 3-7 years of follow-up (56,57). In one study of sequential liver biopsies in 51 kidney transplant recipients every 3-4 years, 40% of the patients had progression of fibrosis, 40% had stable levels of fibrosis, and 20% showed regression of fibrosis .10 years after transplantation (58).…”
Section: Hcv Infectionmentioning
confidence: 99%
“…In several studies where paired liver biopsies were done pre-and posttransplant, the rate of HCV-related fibrosis has been shown to be accelerated in renal transplant recipients when compared to immunocompetent individuals (10,11). When these data are examined more closely, however, the risk of accelerated progression of fibrosis and development of end-stage liver disease and its complications appear to be limited largely to those with advanced fibrosis or cirrhosis at the time of transplant (4,6,9,11).…”
Section: Introductionmentioning
confidence: 99%